The Gut-Brain-Microbiome Axis and Its Link to Autism: Emerging Insights and the Potential of Zebrafish Models - James, David M.; Davidson, Elizabeth A.; Yanes, Julio; Moshiree, Baharak; Dallman, Julia E. (Frontiers in Cell and Developmental Biology, 2021)
Research involving autism spectrum disorder (ASD) most frequently focuses on its key diagnostic criteria: restricted interests and repetitive behaviors, altered sensory perception, and communication impairments. These core criteria, however, are often accompanied by numerous comorbidities, many of which result in severe negative impacts on quality of life, including seizures, epilepsy, sleep disturbance, hypotonia, and GI distress. While ASD is a clinically heterogeneous disorder, gastrointestinal (GI) distress is among the most prevalent co-occurring symptom complex, manifesting in upward of 70% of all individuals with ASD. Consistent with this high prevalence, over a dozen family foundations that represent genetically distinct, molecularly defined forms of ASD have identified GI symptoms as an understudied area with significant negative impacts on quality of life for both individuals and their caregivers. Moreover, GI symptoms are also correlated with more pronounced irritability, social withdrawal, stereotypy, hyperactivity, and sleep disturbances, suggesting that they may exacerbate the defining behavioral symptoms of ASD. Despite these facts (and to the detriment of the community), GI distress remains largely unaddressed by ASD research and is frequently regarded as a symptomatic outcome rather than a potential contributory factor to the behavioral symptoms. Allowing for examination of both ASD’s impact on the central nervous system (CNS) as well as its impact on the GI tract and the associated microbiome, the zebrafish has recently emerged as a powerful tool to study ASD. This is in no small part due to the advantages zebrafish present as a model system: their precocious development, their small transparent larval form, and their parallels with humans in genetics and physiology. While ASD research centered on the CNS has leveraged these advantages, there has been a critical lack of GI-centric ASD research in zebrafish models, making a holistic view of the gut-brain-microbiome axis incomplete. Similarly, high-throughput ASD drug screens have recently been developed but primarily focus on CNS and behavioral impacts while potential GI impacts have not been investigated. In this review, we aim to explore the great promise of the zebrafish model for elucidating the roles of the gut-brain-microbiome axis in ASD.